Chaiwala! - Maheshwari, Priti Birla (Owlkids Books, 2021)
"When their train makes a ten-minute stop at the station in Jaipur, a young girl and her mother hurry to get in line for a cup of chai. The girl orders two cups, and then delights in watching the chaiwala at work--grinding the spices, adding scoops of tea leaves and sugar to the bubbling, boiling milk, then cooling the chai by pouring it from high, back and forth, back and forth--the girl is mesmerized. With a biscuit and a rusk added to their order, mother and child find a spot in the crowded station to rest and enjoy the moment. And that first sip.... aaaahhh. Then it's time to wave goodbye to the chaiwala and hurry back to their train to continue their journey. - The experience of ordering a cup of tea is full of fun sights, sounds, and smells! - A warm, delicious story, rich with sensorial details and authentic experience. - The story was inspired by the author's childhood visits to India, and by the afternoon cup of chai shared daily with her parents. - Illustrator Ashley Barron's amazing paper collage art immerses readers in the colors, sights, scents and sounds of the action at the chaiwala's cart and the train station in Jaipur, India. The art reflects India's diverse population."--